Peranan Game Based Learning dengan Aplikasi Quizizz Dalam Meningkatkan Pembelajaran Bahasa Arab - Fadilah Al Azmi; Himmatul Adzimah; Muhammad Afiq Aminullah; R. Taufiqurrochman (Al-Muyassar: Journal of Arabic Education, 2023)
This study aims to find out how to use Quizizz's role in improving Arabic language learning as a diverse and enjoyable alternative learning. This research is a literature study or literature review with a qualitative descriptive approach by reviewing Quizizz related journals. With the aim of research to explore the role of Quizizz application in improving Arabic language learning. The data sources in this study are several studies related to Quizizz. The data collection technique used is to document several studies related to the title. Meanwhile, the data analysis technique used in this research is content analysis or content analysis. The results of this study are that this application is very relevant and very supportive in assessment activities for learning Arabic, whether in the conch of straightforwardness, speech, lottery, and the book. Likewise, applications are increasingly using learning outcomes that make it easier for students to understand the material, make learning more enjoyable, increase student motivation, interest and independence, and students are more active in learning. Quizizz can be used as a media of assessment and can be complained about using interactive learning materials.